PG130 Can simulation help to translate an internal safeguarding serious incident into multidisciplinary learning?. (10th November 2020) - Conway, Angela; Levi, Claire; Pettit, Katrina; Radley, Ruth; Hamilton, Carrie
Abstract : Introduction: In 2019, an internal safeguarding serious incident inquiry at our Trust identified that healthcare professionals (HCPs) can automatically default to the senior clinician when child protection decisions need to be made promptly. This raised the question: 'How can we empower all HCPs to raise awareness, take responsibility and ensure their concerns are heard, actioned and managed appropriately?' We knew that the answer to this was through education. Our aim was to design, deliver and evaluate interactive workshops to help build confidence and competence when having difficult conversations in the context of safeguarding children. Method: Simulation and safeguarding leads, paediatric specialists, managers and simulated patient (SP) providers developed a sequential scenario which followed the journey of a teenager, from ED admission to Multi Agency Safeguarding Hubs (MASH) referral. The sequence was: information gathering from the teenager (exploring drug trafficking and coercion, leading to collapse), voicing safeguarding concerns to, and challenging decisions of, the duty consultant and informing parent of the MASH referral. The SP provider ensured that the teenager selected for the role was experienced in role portrayal, trained and his advice was sought in depiction of the character. Experts in experiential 'fishbowl' simulation worked with the subject experts at the Trust to ensure effective, safe involvement of SPs. Four workshops ran, for 32 multidisciplinary HCPs from the paediatric wards. Results: Post workshop 100% felt more confident in dealing with safeguarding issues with professional curiosity, challenging professionals' over-optimism and knowledge of criminal exploitation of an older child specifically identified as outcomes. Participants narrative was captured: 'One of the most valuable things I have ever done in my career' 'I now believe in myself' 'Very thought provoking' 'Reinforcing honesty, empathy' 'We need more training like this' Due to the intensity of the roles, the SPs, (teenager, parent and consultant) were fully debriefed and de-roled. They all registered their belief in affecting change for the HCPs. Discussion: Our overall aim was to ensure that children under the age of 18 that have had contact with our Trust are protected. We believe that we have established a clear, meaningful educational workshop that meets this aim. The training lead for the county from the 'Safeguarding Vulnerable Peoples Partnership', attended a session and through further collaboration and looking beyond our professional silos, we plan, together, to develop this training throughout Trust and in conjunction with our multi agency colleagues. References: Department for Education (2018) Working together to safeguard children. Available at: https://www.gov.uk/government/publications/working-together-to-safeguard-children--2 Professional Curiosity (2015) Available at: https://www.preventingexploitationtoolkit.org.uk/guidance-and-support